An improved approach for modeling lightning transients of wind turbines. (October 2018) - Zhang, Xiaoqing; Zhang, Yongzheng; Xiao, Xiang
Highlights: A circuit parameter algorithm is presented for the spatial conductor branches. A truncated pyramid multiconductor system is built for modeling the tower body. An entire circuit model is developed for describing the lightning current path. Lightning transient responses are obtained at different locations of a wind turbine. Abstract: A modeling approach is proposed in this paper for calculating lightning transient responses on wind turbines (WTs). The equivalent circuits are built for blade, dynamic contact part, tower body and grounding system, respectively. The improved tower model discretizes the tower body into a truncated pyramid multiconductor system and can describe the geometrical feature of the actual tower body in a more precise manner. An entire circuit representation is given for the WT by connecting the respective equivalent circuits, from which the lightning transient responses can be obtained. The experimental measurement is also made with a laboratory-scale WT. The validity of the proposed approach is checked by comparing the calculated results with the measured ones. Then, the proposed approach is applied to the lightning transient calculation of an actual WT with 2 MW to predict its potential rise during lightning stroke.